Marketing approach to innovation management as a tool for enhancing innovative activity of enterprises - Bersimbayeva, A.B.; Uruzbayeva, N.A.; Aibossynova, D.A. (Вестник Карагандинского университета, 2017)
First of all, for creating competitive advantages of Kazakhstan enterprises in markets with high competition it is necessary to rethink the scope and role of marketing in management the innovative activity of enterprises. However, in the Kazakh literature there aren’t any special studies devoted to the use of marketing in innova- tion management. As a consequence, the main purpose of this study is to present the importance of using marketing approach in management of innovative activity of enterprises as an effective tool to improve their innovation activity. This paper analyzes the views of domestic and foreign scientists on the role of marketing in the innovation process. On this basis, there is an expediency of using a marketing approach to the man- agement of innovation performance of enterprises. The methodology of the study bases on the hypothesis about the necessity of consideration the category of «management of innovative activity» from the standpoint of an integrated approach – from the point of view of the manufacturer and from the point of view of the con- sumer. Features of this methodology are explained, on the one hand, the complexity of the phenomenon of innovation, the results of which may not always be appreciated by the consumer because of the lack of special knowledge and competencies, as well as the complexity of managing the process, on the other hand. The log- ical conclusion of the work proposed by the authors is the main uses of the marketing concept to improve the innovation activity of enterprises.
Кəсіпорынның инновациялық белсенділігін жоғарылату құралы ретінде инновациялық қызметті басқарудағы маркетингтік тəсіл
Маркетинговый подход к управлению инновационной деятельностью как инструмент повышения инновационной активности предприятий
Keywords: innovative activity; innovative activity of enterprises; management of innovative activity, marketing approach